The Process of Synthesizing Paracetamol Involves the Utilization of Acetic Anhydride to Acetylate p-Aminophenol - Sandrina, Selly; Ahmad Fauzan (Phlox Institute: Indonesian Medical Research Organization, 2023)
The acetylation process using acetic anhydride entails substituting a hydroxyl group (OH) on p-aminophenol with an acetyl group (-COCH3), resulting in the synthesis of paracetamol. In addition to acetic anhydride, this reaction necessitates the presence of a catalyst that enhances the reaction rate for improved efficiency. The objective of this work is to demonstrate the process of synthesizing paracetamol through the acetylation of p-aminophenol using acetic anhydride. The literature search was conducted using multiple databases, including PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar, to explore the synthesis of paracetamol through the acetylation of p-aminophenol using acetic anhydride. A sulfuric acid catalyst is often used to mix p-aminophenol with acetic anhydride in the process of making paracetamol. This approach is commonly employed in the synthesis of paracetamol. Colorimetric analysis, employing FeCl3 solution, is a widely utilized method in analytical chemistry for the identification of specific compounds. This approach relies on the observation and interpretation of color changes that occur during the reaction. The Rf value of 0.88, which is identical to that of pure paracetamol, confirms that the combination of p-aminophenol and acetic anhydride produces the most effective acetylation process with a yield of 59.5% and a high level of purity. The resulting product exhibits a melting point range of 169–170°C and an infrared spectrum that is indistinguishable from that of pure paracetamol.